The price of snow: albedo valuation and a case study for forest management - David A Lutz; Richard B Howarth (Environmental Research Letters, 2015)
Several climate frameworks have included the role of carbon storage in natural landscapes as a potential mechanism for climate change mitigation. This has resulted in an incentive to grow and maintain intact long-lived forest ecosystems. However, recent research has suggested that the influence of albedo-related radiative forcing can impart equal and in some cases greater magnitudes of climate mitigation compared to carbon storage in forests where snowfall is common and biomass is slow-growing. While several methodologies exist for relating albedo-associated radiative forcing to carbon storage for the analysis of the tradeoffs of these ecosystem services, they are varied, and they have yet to be contrasted in a case study with implications for future forest management. Here we utilize four methodologies for calculating a shadow price for albedo radiative forcing and apply the resulting eight prices to an ecological and economic forest model to examine the effects on optimal rotation periods on two different forest stands in the White Mountain National Forest in New Hampshire, USA. These pricing methodologies produce distinctly different shadow prices of albedo, varying from a high of 9.36 × 10 ^−4 and a low of 1.75 × 10 ^−5 $w ^−1 yr ^−1 in the initial year, to a high of 0.019 and a low of 3.55 × 10 ^−4 $w ^−1 yr ^−1 in year 200 of the simulation. When implemented in the forest model, optimal rotation periods also varied considerably, from a low of 2 to a high of 107 years for a spruce-fir stand and from 35 to 80 years for a maple-beech-birch stand. Our results suggest that the choice of climate metrics and pricing methodologies for use with forest albedo alter albedo prices considerably, may substantially adjust optimal rotation period length, and therefore may have consequences with respect to forest land cover change.